Policies to Protect Children during the Pandemic in Indonesia: Between Expectation and Reality - Retno Wulan, Tyas; Dadan, Sulyana; Martono, Nanang; Pandu Primadata, Ankarlina; Ihsan, Alfian (KnE Social Sciences, 2023)
COVID-19 has affected Indonesia in the health aspect and social, economic, and human rights, especially for vulnerable groups. The pandemic also multiplied the injustice experienced by women, children, persons with disabilities, and the elderly. Hundreds of thousands of Indonesians died, experienced by not only the elderly, the most vulnerable group, but also the productive age population. Children have to face two kinds of threats at once, the threat of COVID-19 exposure and the potential of losing their parents. Abandoned forever by their father, mother, or both parents due to exposure to COVID-19, causing many children to be orphaned. According to the data of the Indonesian COVID-19 Handling Task Force, on July 20, 2021, 11,045 children were orphaned. Another data informed that the number of children exposed to COVID-19 was 350,000 children, and 777 children of that died. There are two main purposes of the study to answer the research problem. First, to identify the problems of children as the victims of the COVID-19 pandemic in Indonesia. Second, to map out the policies and stakeholders which are able to provide protection for children as the victims of the COVID-19 pandemic in Indonesia. The results of the study showed that various ministries and national governments have had certain policies to protect children as victims of the COVID-19 pandemic. Still, these policies have not integrated with each other and have not been implemented optimally in the regions.